Co-designing inclusive landscape management plans: a practical guide - Atampugre, Gerald; Tilahun, Seifu A.; Zemadim, Birhanu; Amponsah, Andoh Kwaku; Cofie, Olufunke O.; Mabhaudhi, Tafadzwanashe (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2023)
This report provides a comprehensive guide designed to facilitate the co-design of inclusive landscape management plans. Recognizing the critical role of diverse stakeholder engagement in sustainable land management, the guide offers a detailed framework with a strong focus on practical application. Through a systematic approach, the guide provides step-by-step insights, methodologies, and tools to effectively navigate collaborative processes in landscape management. The central emphasis of the guide lies in promoting inclusivity as a key driver for enhancing the effectiveness and ensuring the long-term success of landscape management initiatives. By offering practical solutions and actionable strategies, the guide serves as a valuable resource for practitioners, policymakers, and community leaders committed to fostering inclusive and participatory approaches in landscape management. This practical resource is tailored for individuals and organizations dedicated to creating landscapes that strike a balance between ecological health, social equity, and economic viability. By emphasizing collaborative design and implementation, the guide aims to contribute to the development of resilient and sustainable landscapes that meet the needs of diverse stakeholders and ensure a harmonious coexistence between nature and society.